Cervical spinal root cavernoma: case report and review. (4th July 2018) - Henderson, Fraser; Skipper, Daniel Carl; Patel, Sunil
Abstract: Aim: Cavernous malformations in the spinal canal are rare. We review previous reports and present our own case of a cervical intradural extramedullary cavernoma, associated with a ventral cervical rootlet. Methods: A 65 year old woman presented with radicular pain and paresthesias of the neck and right arm. PubMed search was used to compare her case to those previously published. Results: The cavernoma was successfully removed with excellent recovery and no deficits. Histopathology confirmed the diagnosis. Conclusion: Gross total resection of symptomatic lesions continues to be the recommended approach, and resection outcomes have restored function in all cases but one, where the deficit persisted.